Multi-objective evaluation of target reliabilities for structural fire design - Chaudhary, Ranjit Kumar; Van Coile, Ruben; ICASP14; Gernay, Thomas (My University, 2023)
Target reliabilities for structural design are mostly informed by risk-based optimization. Such optimization is often computationally challenging, and especially in structural fire engineering involves numerous design parameters, objectives, and constraints. Usually, a single-objective optimization-based approach is adopted, but it is mostly inefficient and could result in uneconomical design solutions. Multi-objective optimization-based approach can address these issues and is therefore considered in the current study for evaluating target reliabilities for the structural fire design. A reinforced concrete slab exposed to natural fires is considered as a case study. The target reliabilities for the slab vary between 1.0 and 4.0 for the structural fire design. The consideration of the environmental cost does not influence the result of cost optimization in RC slab except in the case of a higher trade-off of CO2 emission with dollars, while post-fire repairability considerations result in a significantly increased target reliability level.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED